A Randomized Controlled Trial on the Efficacy of a Psychosocial Behavioral Intervention to Improve the Lifestyle of Patients With Severe Mental Disorders: Study Protocol - Sampogna, Gaia; Fiorillo, Andrea; Luciano, Mario; Del Vecchio, Valeria; Steardo, Luca; Pocai, Benedetta; Barone, Marina; Amore, Mario; Pacitti, Francesca; Dell'Osso, Liliana; Di Lorenzo, Giorgio; Maj, Mario; et al. (Frontiers in Psychiatry, 2018)
Patients with severe mental disorders die on average 20 years prior to the general population. This mortality gap is mainly due to the higher prevalence of physical diseases and the adoption of unhealthy lifestyle behaviours. The LIFESTYLE trial aims to evaluate the efficacy of a new psychosocial group intervention (including psychoeducational, motivational and problem-solving techniques) focused on healthy lifestyle behaviour compared to a psychoeducational brief group intervention in a community sample of patients with severe mental disorders. The trial is a national-funded, multicentric, randomized controlled trial with blinded outcome assessments, which is carried out in six outpatient units of the Universities of Campania “Luigi Vanvitelli” in Naples, Bari, Genova, L’Aquila, Pisa and Rome - Tor Vergata. All patients are assessed at the following time points: baseline (T0); 2 months post-randomization (T1); after 4 months post-randomization (T2); 6 months post-randomization (T3); 12 months post-randomization (T4) and 24 months post-randomization (T5). T1 and T2 assessments include only anthropometric tests. The BMI, a reliable and feasible anthropometric parameter, has been selected as primary outcome. In particular, the mean value of BMI at 6 months from baseline (T3) will be evaluated through a Generalized Estimated Equation model. The work hypothesis is that the experimental intervention will be more effective than the psychoeducational group intervention in reducing the BMI. We expect a mean difference between the two groups of at least one point (and standard deviation of 2 points) at BMI. Secondary outcomes are: the improvement in dietary patterns, in smoking habits, in sleeping habits, physical activity, personal and social functioning, severity of physical comorbidities and adherence to medications. The expected sample size consists of 420 patients (70 patients for each of the six participating centre), and they are allocated with a 1:1 ratio randomization, stratified according to centre, age, gender and educational level, allocated to the the two groups. Heavy smoking, sedentary behaviour and unhealthy diet pattern are very frequent and are associated with a reduced life expectancy and higher levels of physical comorbidities in people with severe mental disorders. New interventions as the LIFESTYLE protocol are needed to fill such gap.